Wear resistance of injection-molded thermoplastic denture base resins - Ippei Hamanaka; Misa Iwamoto; Lippo V. J. Lassila; Pekka K. Vallittu; Yutaka Takahashi (Taylor & Francis Group, 2016)
Objective This study investigated the wear resistance of injection-molded thermoplastic denture base resins using nanoindentation instrument. Materials and methods Six injection-molded thermoplastic denture base resins (two polyamides, two polyesters, one polycarbonate, one polymethylmethacrylate [PMMA]) and a PMMA conventional heat-polymerized denture-based polymer control were tested. Elastic modulus, hardness, wear depth, and roughness were calculated using a nanoindentation instrument. Results Elastic modulus and hardness of the injection-molded thermoplastic denture base resins were significantly lower than those of the PMMA conventional heat-polymerized denture-based polymer. Wear depth of polycarbonate and PMMA conventional heat-polymerized denture-based polymer were significantly higher than that of other injection-molded thermoplastic denture base resins. The roughness of injection-molded thermoplastic denture base resins was significantly more than that of PMMA conventional heat-polymerized denture-based polymer after testing. Conclusions Wear resistance of injection-molded thermoplastic denture base was low compared to PMMA conventional heat-polymerized denture-based polymers.